Tuning the surface chemistry of graphene flakes: new strategies for selective oxidation. Issue 23 (3rd March 2017) - Araújo, Mariana P.; Soares, O. S. G. P.; Fernandes, A. J. S.; Pereira, M. F. R.; Freire, C.
Abstract : One-step selective oxidation strategies towards the rational tuning of the surface chemistry of graphene flakes are presented. Abstract : To accomplish a rational tuning of the surface chemistry of graphene flakes (GF), four different one-step protocols towards the selective oxidation of GF were performed, using different oxidants: nitric acid, potassium permanganate/sulfuric acid, ozone and 3-chloroperbenzoic acid. The characterization of the resulting materials confirmed the successful preparation of oxidized GF with C/O atomic ratios varying in the range of 21.2–4.9, with distinct types of oxygen functionalities. While the oxidation of GF with nitric acid exclusively promotes the introduction of carboxylic groups and carbonyl/quinones, 3-chloroperbenzoic acid is responsible for the introduction of epoxyl groups and carboxylic anhydrides, potassium permanganate favours the introduction of epoxyl and hydroxyl groups and some content of carboxylic anhydrides, and ozone promotes predominantly the introduction in graphene structure of epoxyl groups, carboxylic anhydrides, phenols, quinones and lactones, and in a lesser extension carbonyl groups in α-substituted ketones and aldehydes if the oxidation is performed in the solid phase, or hydroxyl groups and a moderate content of carbonyl groups and aldehydes if GF are in a water dispersion. Furthermore, this work highlighted the possibility of identifying and distinguishing labile groups, namely hydroxyl and epoxyl groups, which are predominant in the structure of GF oxidized with potassium permanganate/sulfuric acid, ozone and 3-chloroperbenzoic acid. This is the first comprehensive study on the fine tuning of the surface of oxidized GF and a major contribution for the rational design of graphene composites since the application of these specific strategies can be useful in the anchoring of other molecules or nanoparticles.